District of Columbia community health needs assessment - Chandra, Anita (Research report, 2013)
The District of Columbia Healthy Communities Collaborative (DCHCC) represents a unique collaboration among D.C.-area hospitals and federally qualified health centers. In response to its community commitment and Affordable Care Act requirements, DCHCC set forth to conduct a community health needs assessment (CHNA) that can guide decisions about where and how to allocate resources and implement appropriate health interventions for the population it serves. The CHNA described in this report includes analysis of existing demographic, health status, and hospital service use data, as well as hospital and emergency department discharge data. The analysis of this quantitative data is complemented by an analysis of current stakeholder perspectives regarding health needs, as well as health policy and investment priorities. This CHNA demonstrates the persistence of many issues identified in prior CHNAs: asthma, obesity, mental health, and sexual health. Despite high insurance rates, health care services are not evenly distributed by ward, creating significant challenges to access. There is a need to expand these services, as well as improve care coordination between health and social services to help residents navigate the system and obtain the services they need. In addition to these intervention pathways by priority health condition, we identified emerging issues that require further investigation, including declines in coronary atherosclerosis discharges and a spike in stress-related diagnoses (headaches and back pain) and associated alcohol-related issues. This may be related to a host of factors, including economic downturn and demographic transitions in the District.